Development of Augmented Reality in Islamic Religious Education Learning: Case Study in Islamic Boarding School-Based Schools - Nasikhin, Nasikhin; Murtadho, Ali; Syukur, Fatah; de Cómputo, Escuela Superior; Roya, Abdul; Hasan, Zainudin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
This research aims to develop interactive learning media based on augmented reality to improve cognitive abilities in Islamic boarding school-based schools. This research and development type research uses the ADDIE development design through the analysis, design, development, implementation and evaluation stages. This research involved 94 students who collected data through tests, questionnaires and observations. Qualitative data was analyzed using the Miles and Huberman approach, while quantitative data was analyzed using the Paired Sample T-test. This study shows that the use of Augmented Reality learning media has a positive impact on students' cognitive abilities. The significant difference between the pretest and posttest scores, an average of -12.98, shows a significant increase after using this media. The standard deviation of 8.50539 indicates variation in improving results between students. However, with a 95% confidence interval, the difference between pretest and posttest scores was in the range -15.96 to -10.02, confirming a significant change. The results of the t-test hypothesis test (t=8.905, df=33) with a low p value (0.002) confirm that Augmented Reality media significantly increases student achievement in this trial. With these results, Islamic boarding school education policies can consider the integration of Augmented Reality as a learning medium that supports students' academic development more effectively.